Misliti medkulturno literarno zgodovino na Slovenskem - Skapin, Anja (Primerjalna književnost, 2020)
This contribution addresses interculturalism as an issue of literatures in intra- and intersubjective as well as in intra- and interdiscursive contact, while also shedding light on some possibilities for expanding Slovenian literary history and its canon. It focuses on the after independence era, when on the one hand there was an increased interest in exploring the past, and on the other, the directions of a homogeneously oriented (global) book market were beginning to emerge. After independence, Slovenia is still facing two turning points: how to maintain its identity, which at the time was completely in the hands of state autonomy; and how a small nation and a small literature to be visible after the fall into the rapidly growing global book market. Based on the model of intercultural literary science, one can see how the self and the alien interweave at all levels of human action, and what impact this has on the construction of a dynamic identity and a dynamic literary canon.
Keywords: globalizacija; kulturna identiteta; kulturni spomin; literarna zgodovina; literarni kanon; medkulturnost; Slovenija; tradicija; tujost